Nekaj misli o spoštovanju Ustave in ravnanju v skladu z njo v našem vsakdanu - Sovdat, Jadranka (Pravnik, 2024)
The author emphasises the foundational elements of the constitutional order, among them human rights, human dignity, and fundamental constitutional principles. These elements impose obligations on every person and the bearers of different branches of the state power. People are aware of the human rights they are entitled to, but they have to exercise them responsibly and with respect for human rights and human dignity of every other person. The bearers of the state power must remain acutely aware, besides to above, of the significance and mission of their office in the system of state power. The constitutionally determined competences that they have to exercise in conformity with the constitutional order are their constitutional duties. The principle of the separation of powers forbids any branches of power from omitting its own constitutional functions. When state institutions, including the legislator, disregard decisions of the courts and the Constitutional Court, they undermine the very foundations of the constitutional order. Therefore, the legislator and the government have to respond to every single decision of the Constitutional Court which establishes unconstitutionality of a statute provisions within the period determined by the Constitutional Court that the unconstitutionality be remedied on time and the human rights of the addressees of legal provisions be protected.
Keywords: constitutional duties of the bearers of state powers; človekove pravice; fundamental constitutional principles; human rights; načelo ločitve oblasti; respect for decisions of the Constitutional Court; spoštovanje odločb ustavnega sodišča; temeljna ustavna načela; the principle of the separation of powers; the rule of law; ustavne dolžnosti nosilcev državne oblasti; vladavina prava